Exploring lesbian, gay and bisexual patients' accounts of their experiences of cancer care in the UK. (20th April 2016) - Fish, J.; Williamson, I.
Abstract : Despite greater recognition of rights and responsibilities around the care of cancer patients who identify as lesbian, gay or bisexual (LGB) within healthcare systems in the United Kingdom, recent quantitative evidence suggests that they experience poorer care than heterosexual counterparts and qualitative findings are limited. Therefore, in the present study, we present an analysis of the accounts of fifteen British LGB cancer patients (diagnosed with different forms of the disease) of the care received. Data were collected through in‐depth individual interviews and analysed using thematic analysis. Three of the emerging themes are discussed. These include an examination of what we conceptualise as the 'awkward choreography around disclosure' opportunities and dilemmas for LGB patients, we describe 'making sense of sub‐optimal care' which included instances of overt discrimination but was more frequently manifested through micro‐aggressions and heteronormative systems and practices, and explore accounts of 'alienation from usual psychosocial cancer support'. We employ Meyer's Minority Stress Theory (2003) as a lens to interrogate the data and explore the ways in which actual or anticipated prejudice affected their experiences of treatment and support. We close with recommendations to enhance LGB‐affirmative cancer care including enhanced training of healthcare professionals and explicit articulation of institutional commitment to LGB equality.